Reliability Design of Mechanical Systems Subject to Repetitive Stresses - Woo, Seong-Woo; L. O128;™Neal, Dennis (Recent Patents on Mechanical Engineering, 2015)
The basic reliability concepts - parametric ALT plan, failure mechanism and design, acceleration factor, and sample size equation were used in the development of a parametric accelerated life testing method to assess the reliability quantitative test specifications (RQ) of mechanical systems subjected to repetitive stresses. To calculate the acceleration factor of the mechanical system, a generalized life-stress failure model with a new effort concept was derived and recommended. The new sample size equation with the acceleration factor also enabled the parametric ALT to quickly evaluate the expected lifetime. This new parametric ALT should help an engineer uncover the design parameters affecting reliability during the design process of the mechanical system. Consequently, it should help companies improve product reliability and avoid recalls due to the product failures in the field. As the improper design parameters in the design phase are experimentally identified by this new reliability design method and recent patents are addressed, the mechanical system should improve in reliability as measured by the increase in lifetime, LB, and the reduction in failure rate, λ.
Keywords: failure mechanics